Detection of allele frequencies of common c. 511C>T and c.625G>A variants in the ACADS gene in the Turkish population - Kılıç, Mustafa; Ergüner, Bekir; Koşukçu, Can; Özgül, Rıza Köksal (The Turkish Journal of Pediatrics, 2020)
Short-chain acyl-CoA dehydrogenase deficiency (SCADD) is a rare inborn error of mitochondrial fatty acid oxidation and protein misfolding disorder. Our aim was to detect the number of Turkish patients diagnosed with SCADD in the literature and to determine the allele frequencies of two common variants (c.511C > T and c.625G > A) in the Turkish population. Five Turkish patients with SCADD were reported in the literature from four unrelated families. We also investigated allele frequencies of common variants of c.511C > T and c.625G > A, which confer susceptibility to SCADD, which were found to be 1.7% and 20.2%, respectively. Both of these susceptibility variants were found to be high in the Turkish population as they are worldwide.
Keywords: ACADS; SCAD; SCAD deficiency; SCADD; ethylmalonic aciduria; short-chain acyl-CoA dehydrogenase deficiency